Function and mechanism of tumor suppressor gene LRRC4/NGL-2 - Li, Peiyao (BioMed Central, 2014)
LRRC4/NGL-2 (Leucine rich repeat containing 4/Netrin-G ligand-2), a relatively specific expressed gene in brain tissue, is a member of the LRRC4/ NGL (netrin-G ligand) family and belongs to the superfamily of LRR proteins. LRRC4/NGL-2 regulates neurite outgrowth and lamina-specific dendritic segmentation, suggesting that LRRC4/NGL-2 is important for the development of the nervous system. In addition, LRRC4/NGL-2 has been identified as a tumor suppressor gene. The overexpression of LRRC4/NGL-2 suppresses glioma cell growth, angiogenesis and invasion through complicated signaling regulation networks. LRRC4/NGL-2 also has the ability to form multiphase loops with miRNA, transcription factors and gene methylation modification; the loss of LRRC4/NGL-2 function may be an important event in multiple biological processes in gliomas. In summary, LRRC4/NGL-2 is a critical gene in the normal development and tumorigenesis of the nervous system.